Tendência clean label: uma revisão - OLIVEIRA, Thaís Andrade de (2022)
Currently, consumers are more frequently looking for quality foods that contain natural ingredients, with reduced or excluded additives and that offer greater nutritional support. However, there is still some difficulty in the search for processed foods, which are practical and healthy, since consumers often do not understand the complex list of ingredients on the food label. With this demand, the so-called “clean label” foods appear, in the literal translation “clean label”. Given the above, the present work aims to highlight the importance of the clean label trend, as well as highlight its characteristics and its relationship with changes in eating habits of society. The methodology used was a bibliographic review, of the integrative type, through research carried out in scientific articles, current Brazilian health legislation, electronic journals, among others. The clean label trend aims to facilitate the consumer's understanding of the product information contained on the label and can also cover several other characteristics associated with healthiness. Thus, it is concluded that the clean label trend refers to products made with as few ingredients as possible, using mainly or exclusively ingredients that consumers can easily recognize and identify as healthy, where it gained strength as society became concerned with health and quality of life issues, directly impacting changes in eating habits and food choices.